2021
DOI: 10.1177/03635465211025002
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Exercises for Dysfunction of the Scapula: Exploration of Muscle Activity Using Fine-Wire EMG

Abstract: Background: Scapular muscle activity during shoulder exercises has been explored with surface electromyography (EMG). However, knowledge about the activity of deeper-layer scapular muscles is still limited. Purpose: To investigate EMG activation of the deeper-layer scapular stabilizers (levator scapulae [LS], rhomboid major [RM], pectoralis minor [Pm] muscles) together with superficial muscle activity (upper [UT], middle [MT], and lower trapezius [LT] and serratus anterior [SA]) during 4 exercises often used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…The present investigation had limitations: (i) this report was based only on the EMG activity normalized by MVIC and did not consider the UT/SA ratio as a valid outcome measure for inter-subject comparisons. This measurement has been widely reported as the outcome that allows making comparisons between individuals and exercises, as well as this allows evaluating and analyzing the intra and inter-muscular balance ( Ludewig et al, 2004 ; Berckmans et al, 2021 ); (ii) as reported by other reviews ( Kang et al, 2019 ; Mendez-Rebolledo et al, 2021 ) most of the included studies did not present a priori a sample size or the statistical power of the analyzes, and they recruited participants healthy and asymptomatic, which make difficult to fully extrapolate the results of this research to populations with shoulder musculoskeletal dysfunctions; (iii) 93,3% the included studies showed a moderate methodological quality, mainly due internal validity aspects; and (iv) the present investigation was not able to carry out a meta-analysis for the push-up plus exercise, considering that add scapular protraction may increment the myoelectrical activity of the SA, involved directly in this movement. Finally, and according to GRADE, the certainty of evidence ranged from “very low” to “low” for the outcomes, harming the confidence in the presented estimates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present investigation had limitations: (i) this report was based only on the EMG activity normalized by MVIC and did not consider the UT/SA ratio as a valid outcome measure for inter-subject comparisons. This measurement has been widely reported as the outcome that allows making comparisons between individuals and exercises, as well as this allows evaluating and analyzing the intra and inter-muscular balance ( Ludewig et al, 2004 ; Berckmans et al, 2021 ); (ii) as reported by other reviews ( Kang et al, 2019 ; Mendez-Rebolledo et al, 2021 ) most of the included studies did not present a priori a sample size or the statistical power of the analyzes, and they recruited participants healthy and asymptomatic, which make difficult to fully extrapolate the results of this research to populations with shoulder musculoskeletal dysfunctions; (iii) 93,3% the included studies showed a moderate methodological quality, mainly due internal validity aspects; and (iv) the present investigation was not able to carry out a meta-analysis for the push-up plus exercise, considering that add scapular protraction may increment the myoelectrical activity of the SA, involved directly in this movement. Finally, and according to GRADE, the certainty of evidence ranged from “very low” to “low” for the outcomes, harming the confidence in the presented estimates.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely recognized that scapular dyskinesis rehabilitation programs focused on decreasing UT activation and increasing SA and LT activation in early stages of the rehabilitation process contribute to restoring normal scapular position and movement ( Cools et al, 2007 ; Youdas et al, 2020b ; Berckmans et al, 2021 ). Several closed kinetic chain exercises have been reported as efficient to increase SA and LT myoelectrical activity, such as “push-up” ( Calatayud et al, 2014a ; Santos et al, 2018 ), “push-up plus” (scapular protraction posture in the end of the ascending phase of a push-up) ( Cools et al, 2014 ; Batbayar et al, 2015 ; Gioftsos et al, 2016 ; Hwang et al, 2017 ), “scapular protraction” (scapular protraction and retraction with elbows extended) ( Andersen et al, 2012 ; Lee, Lee & Park, 2013 ; De Mey et al, 2014 ), and “plank” (prone position, with the trunk and leg fully extended, the shoulders flexed at 90° and elbows in extension) ( Pontillo et al, 2007 ; Tucker et al, 2010 ; Ashnagar et al, 2016 ; Oliver et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a standardized method to assess the sensorimotor function of the shoulder is yet to be determined. Other commonly used methods are the joint position sense and kinesthesia examinations [26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…And EMG signals are measured to determine the electrical current generated by muscle contractions in neuromuscular activity [46]. Therefore, electromyography (EMG) is often used as a tool to determine muscle activity [47][48][49][50]. Bogey et al [44,51] recently developed a method to estimate force from EMG signals and based on normalization of activation during maximum voluntary contraction to record maximum muscle force.…”
Section: Muscle Analysismentioning
confidence: 99%